Robot-assisted excision with intervertebral foramen endoscopy in the treatment of osteoid osteoma of femoral neck: a case report - Jinying Lao; Gen Ba; Tianjing Liu; Enbo Wang (Frontiers in Pediatrics)
BackgroundThe diaphyseal or metaphyseal of the long bone is a common location for osteoid osteoma(OO), however, the femoral neck lesion is rare. There proves an original method to treat this disease.Case presentationAn 11-year-old female, complained of a limp and right hip pain. Based on her history, and clinical and imaging examination, she was diagnosed with OO. Given that the location of the lesion is on the back of the femoral neck within the hip joint, and the local anatomical structure is close to the sciatic nerve and medial circumflex femoral artery, we performed robot-assisted excision with intervertebral foramen endoscopic.ConclusionsThis innovative treatment completely and successfully eliminated her symptoms without recurrence at the last follow-up. Our research suggests that this technology can be widely applied to the treatment of OO at some sites difficult to reach, beyond other orthopedic conditions.